DESIGNING MICROLEARNING OBJECT MATERIAL OF ENGLISH READING MATERIAL FOR SENIOR HIGH SCHOOL - Putra, Harbi; Iskandar, Ifan; Sumarni, Sri (TELL - US JOURNAL, 2023)
By providing students with brief and focused learning resources, microlearning has been touted as a potential means of fostering critical thinking in learners. To increase students' reading abilities at the fundamental grade 10 level according to the CEFR Level, the aim of this study is to give an overview of how critical thinking is incorporated in the use of microlearning material objects. The results are anticipated to be used as a guide by the corporate community, government, and academia in promoting, developing, and putting into practice microlearning in English reading. Two different sets of analysis were performed for this investigation. The author begins by reviewing the instructional materials of English Reading in light of the Kurikulum Merdeka. The author also looks at the stages of adopting microlearning in learning from a variety of sources. According to the results of the reviews on microlearning, there are various methods and forms of microlearning that may be utilized to create learning materials for reading. From a work-based learning standpoint, microlearning has been identified as a key topic in talent development. To assist people in learning on the correct road through accurate knowledge and ethical reasoning, policy makers, educators, researchers, and participants should look into strategies to encourage, generate, and apply microlearning.